PENERAPAN MODEL KOOPERATIF TALKING CHIPSBERBANTUAN MOLYMOD UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - Wulandari, Eka; Melati, Husna Amalya; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract:Â The purpose of this research was to improve the activity and student learning outcomes in learning chemistry material especially hydrocarbons using cooperative learning model type chips talking with media aided molymod simple. This research is a classroom action research that teachers as teachers and researchers along with four observers observe the process of learning that takes as much as two cycles. Subjects in this study were class XB SMA Negeri 4 Sungai Raya consists of 33 students. Data was collected by using a measurement technique of learning outcomes and observations. Indicators of success of this study of pre-action to do the first cycle and the second cycle is an increase in activity and student learning outcomes of â‰¥50%. The results showed that the use of cooperative learning model talking chips aided simple molymod media can increase the activity and student learning outcomes. The percentage of student activity increased from 31.66% in the first cycle to 51.66% in the second cycle. The percentage of student learning outcomes increased from 48.48% in the first cycle to 84.84% in the second cycle.Â Key Words:Talking chips, Molymod, Hidrokarbon,Activity, Student learning.